2020
DOI: 10.3390/ani10122253
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Mycotoxins from Lactation Feed to Colostrum of Sows

Abstract: Studies regarding the transfer of mycotoxins from sow feed to colostrum are scarce. A sample of in-house produced lactation feed and one of colostrum were collected from two or three sows per farm (total 49) from 19 farms. The feed contents of aflatoxins (AFs), fumonisins (FUs), deoxynivalenol (DON) and zearalenone (ZEA) were assessed using ELISA and confirmed by liquid chromatography-mass spectrometry (LC-MS), The values were very low (10, 12, 17 and 2 positive samples for AFs, FUs, DON and ZEA, respectively)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
(31 reference statements)
0
2
0
1
Order By: Relevance
“…Regarding DON and de-DON, they have been previously identified in the colostrum and serum from sows [ 16 ]. In a recent study, Trevisi et al [ 17 ] demonstrated the transfer of dietary DON to the colostrum of sows fed naturally contaminated diets containing this mycotoxin at levels ranging from 60 to 438 ppb.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding DON and de-DON, they have been previously identified in the colostrum and serum from sows [ 16 ]. In a recent study, Trevisi et al [ 17 ] demonstrated the transfer of dietary DON to the colostrum of sows fed naturally contaminated diets containing this mycotoxin at levels ranging from 60 to 438 ppb.…”
Section: Discussionmentioning
confidence: 99%
“…Such exposure may even occur via the placenta and/or during lactation ( 3 ). The presence of DON and its metabolite de-epoxy-DON (de-DON) was detected in the colostrum of sows ( 4 , 5 ). Recently, DON, ZEN, and their metabolites were identified in the colostrum, milk, and serum of sows fed diets containing 250 ppb DON and 100 or 300 ppb ZEN ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nos machos alimentados com fumonisina nas fases de crescimento e puberdade, fornecida na quantidade de 5 a 15mg/kg de FB1, os animais apresentaram menor consumo de ração e menor ganho de peso, fatores que impactaram diretamente a idade na maturidade sexual, sendo necessário 30 dias adicionais para atingirem o mesmo índice quando comparado com os animais que estavam no grupo controle (Gbore, 2009). Nas fêmeas em fase de lactação, recebendo ração naturalmente contaminada com baixos níveis de fumonisina, inferiores a 3,74 mg/kg, a micotoxina foi transferida para o colostro sendo positiva em 45% das amostras avaliadas e, mesmo em baixos níveis, este contato do leitão recém-nascido com a fumonisina é um fator de risco para a produção animal (Trevisi et al, 2020).…”
Section: Fumonisinas Na Alimentação De Suínosunclassified